Nanoparticles Alter Secondary Metabolism in Plants via ROS Burst - Marslin, Gregory; Sheeba, Caroline J.; Franklin, Gregory (Frontiers in Plant Science, 2017)
The particles within the size range of 1 and 100 nm are known as nanoparticles (NPs). NP-containing wastes released from household, industrial and medical products are emerging as a new threat to the environment. Plants, being fixed to the two major environmental sinks where NPs accumulate — namely water and soil, cannot escape the impact of nanopollution. Recent studies have shown that plant growth, development and physiology are significantly affected by NPs. But, the effect of NPs on plant secondary metabolism is still obscure. The induction of reactive oxygen species (ROS) following interactions with NPs has been observed consistently across plant species. Taking into account the existing link between ROS and secondary signaling messengers that lead to transcriptional regulation of secondary metabolism, in this perspective we put forward the argument that ROS induced in plants upon their interaction with NPs will likely interfere with plant secondary metabolism. As plant secondary metabolites play vital roles in plant performance, communication, and adaptation, a comprehensive understanding of plant secondary metabolism in response to NPs is an utmost priority.